Dietary yeast glycoprotein supplementation improves the growth performance, intestinal health and disease resistance of largemouth bass (Micropterus salmoides) fed low-fishmeal diets - Cai, Wanjie; Fu, Lele; Liu, Haokun; Yi, Jianhua; Yang, Fan; Hua, Luohai; He, Linyue; Han, Dong; Zhu, Xiaoming; Yang, Yunxia; Jin, Junyan; Dai, Jinjun; et al. (Frontiers in Immunology, 2023)
The active ingredients extracted from yeast are important for regulating animal health. The aim of the current research was to explore the impacts of dietary yeast glycoprotein (YG) on the growth performance, intestinal morphology, antioxidant capacity, immunity and disease resistance of largemouth bass (Micropterus salmoides). A total of 375 juvenile fish (6.00 ± 0.03 g) were allocated into 15 fibreglass tanks. Triplicate tanks were assigned to each diet. The dietary YG inclusion was as follows: the first group was given a high fishmeal diet (40% fishmeal, 0% YG) (FM) and the second group was given a low fishmeal diet (30% fishmeal and 15% soybean meal, 0% YG) (LFM). The fish in the third, fourth and fifth groups were fed the LFM diet supplemented with 0.5% (LFM+YG0.5), 1.0% (LFM+YG1.0) and 2.0% (LFM+YG2.0) YG, respectively. After a 60- day feeding trial, a challenge test using A. hydrophila was carried out. The results showed that the final body weight (FBW) and weight gain rate (WGR) in the LFM+YG2.0 group were significantly higher than those in the LFM group and were no significantly different from those in the FM group. This may be partially related to the activation of the target of rapamycin (TOR) signalling pathway. Dietary YG supplementation enhanced intestinal physical barriers by upregulating the intestinal tight junction protein related genes (claudin1, occludin and zo2) and improving the structural integrity of the gut, which may be partially associated with AMPK signaling pathway. Moreover, dietary YG increased the antioxidant capacity in the gut, upregulated intestinal anti-inflammatory factors (il-10, il1-1β and tgf-β) and downregulated proinflammatory factors (il-1β and il-8), which may be partially related to the Nrf2/Keap1 signalling pathways. The results of the challenge test indicated that dietary supplementation with 0.5 or 1.0% YG can increase the disease tolerance of largemouth bass against A. hydrophila. In conclusion, the present results indicated that dietary supplementation with YG promotes the growth performance, intestinal immunity, physical barriers and antioxidant capacity of largemouth bass. In addition, 1.0% of dietary YG is recommended for largemouth bass based on the present results.